Cavity-mediated interactions between the guided mode resonance and surface phonon polaritons in a hybrid photonic–phononic system. (2nd July 2018) - Zheng, Gaige; Zou, Xiujuan; Xian, Fenglin; Xu, Linhua
Abstract: A strong mode coupling between the guided mode resonance (GMR) and surface phonon polaritons (SPhPs) is numerically demonstrated. The photonic–phononic mode coupling can be mediated by a homogeneous spacer which works as a Fabry–Pérot (FP) cavity, and its strength, manifested by mode splitting and bending of dispersion curves, can be tuned flexibly by adjusting the thickness of the FP cavity. This mode-coupling effect can be used to control the near-field localization sites in this hybrid structure, which provide useful implications for manipulating infrared electromagnetic near fields in nanophotonics devices.